Removal Of SO2 And NO From Simulated Flue Gas Using Cerium-Modified Palm Shell Activated Carbon - Sethupathi, Sumathi (2010)
The focus of this research was to study the usage of oil palm shell made activated carbon as a sorbent to remove SO2 and NO gases simultaneously from simulated flue gas. The palm oil industry plays a major role in Malaysian economic especially in enhancing the economic welfare of the population. Despite obvious benefits of this industrial development, its activity contributes to abundant solid waste. Palm shell derived from the fruit bunch of oil palm, is one of the solid wastes.